2011
DOI: 10.1152/japplphysiol.00634.2010
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional map of the impact of endurance exercise training on skeletal muscle phenotype

Abstract: The molecular pathways that are activated and contribute to physiological remodeling of skeletal muscle in response to endurance exercise have not been fully characterized. We previously reported that ∼800 gene transcripts are regulated following 6 wk of supervised endurance training in young sedentary males, referred to as the training-responsive transcriptome (TRT) (Timmons JA et al. J Appl Physiol 108: 1487-1496, 2010). Here we utilized this database together with data on biological variation in muscle adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
224
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 215 publications
(244 citation statements)
references
References 69 publications
15
224
2
3
Order By: Relevance
“…For example, previous evidence indicates that PGC-1a mRNA accumulates with endurance training, while studies of PGC-1a protein reflect various antibodies that measure distinct molecular entities ranging from 70 to >110 kDa [78][79][80] . Furthermore, mice lacking PGC-1a adapt normally to endurance exercise training, and in humans the PGC-1a regulated gene network does not correlate with aerobic adaptation 69 . Thus any argument that places Irisin as part of the core PGC-1a regulated exercise adaptation program needs to reflect, on both technical and theoretical grounds, that there is great uncertainty of the nature and importance of PGC-1a in exercise and health 81 .…”
Section: Summary Of the Main Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, previous evidence indicates that PGC-1a mRNA accumulates with endurance training, while studies of PGC-1a protein reflect various antibodies that measure distinct molecular entities ranging from 70 to >110 kDa [78][79][80] . Furthermore, mice lacking PGC-1a adapt normally to endurance exercise training, and in humans the PGC-1a regulated gene network does not correlate with aerobic adaptation 69 . Thus any argument that places Irisin as part of the core PGC-1a regulated exercise adaptation program needs to reflect, on both technical and theoretical grounds, that there is great uncertainty of the nature and importance of PGC-1a in exercise and health 81 .…”
Section: Summary Of the Main Resultsmentioning
confidence: 96%
“…One of the included studies 20 found no effect of chronic exercise on PGC1a or FNDC5 mRNA in younger adults (despite detecting significant changes in ~1,000 other mRNAs and finding mitochondrial enzyme activity was increased in ~25%) 69 . Similarly, an 8-week resistance exercise program did not alter PGC-1a or FNDC5 mRNA in muscle of young healthy adults 64 .…”
Section: Reporting Of the Outcomesmentioning
confidence: 98%
“…Subsequently, from a panel of 3,400 SNPs in the HERITAGE study cohort, several DNA variants showed associations with the trainability of maximal aerobic power. However, after the conservative Bonferroni correction, none of the SNPs remained statistically significant (26). In the rat model, selected from 10 generations of high responders to aerobic training, there was evidence to the effect that in these animals the TRT and a subset of the human high-responder genes were regulated to a greater degree in the high-responder rodents.…”
Section: Endurance Performancementioning
confidence: 97%
“…These transcripts were identified as the training-responsive transcriptome (TRT) (43). In the more recent publication, the same group studied the potential regulatory molecules coordinating the complex network of exercise-training regulated genes using different cohorts, including 24 sedentary and healthy men who performed 6 weeks of endurance training (26). In addition, genotyping was performed on 473 white subjects from the HERITAGE cohort (6), and a novel outbred rodent aerobic capacity model was studied.…”
Section: Endurance Performancementioning
confidence: 99%
See 1 more Smart Citation